2011
DOI: 10.1080/10503307.2010.539284
|View full text |Cite
|
Sign up to set email alerts
|

Expert reasoning in psychotherapy case formulation

Abstract: Therapist reasoning in case formulation construction was investigated. Sixty-five psychodynamic or cognitive-behavioral therapists classified as experts, experienced, or novices generated "think aloud" formulations based on six standardized vignettes. Formulations were reliably transcribed, segmented into idea units, and content coded. ANOVA and sequential analysis compared formulation content and reasoning processes. Expert formulations contained more descriptive, diagnostic, inferential, and treatment planni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 35 publications
2
40
0
2
Order By: Relevance
“…However, training and therapist experience have consistently been found to impact on the quality of formulations for clinicians working with either cognitive behavioral or psychodynamic frameworks [14]. Encouragingly, Kendjelic & Eells [15] reported that even brief clinician training produced '... formulations rated as higher in overall quality and as more elaborated, comprehensive, complex, and precise' (p.66).…”
Section: Cautions Regarding Formulationmentioning
confidence: 99%
“…However, training and therapist experience have consistently been found to impact on the quality of formulations for clinicians working with either cognitive behavioral or psychodynamic frameworks [14]. Encouragingly, Kendjelic & Eells [15] reported that even brief clinician training produced '... formulations rated as higher in overall quality and as more elaborated, comprehensive, complex, and precise' (p.66).…”
Section: Cautions Regarding Formulationmentioning
confidence: 99%
“…Therefore, case formulations can be reviewed for their quality (McMurran et al, ) in terms of the extent to which they are understood by others and/or the extent to which they yield detailed and testable predictions about recommended interventions and their likely effectiveness (Hart et al, ). Expertise in case formulation has been associated with theory‐driven inferential reasoning (‘if … then’), in contrast to explanations which simply attempt to account for actions in the past (‘because…’), (Eells et al, ).…”
Section: Forensic Case Formulation In Hospital Settings: Some Implicamentioning
confidence: 99%
“…The presence of inferential reasoning which characterizes a good level of expertise in formulation requires a solid knowledge base [16]. Psychiatric formulation is an example of how a learner evolves through the six levels of thinking in Bloom's taxonomy pyramid (remembering, understanding, applying, analyzing, evaluating and creating) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Mace & Binyon [8] have outlined 4 levels to aid in the development of the skill of formulation: recognizing the psychological dimension (difficulties relating to events, reactions and relationships); constructing an illness narrative (story linking past and present); modeling a formulation (structured understanding of causative factors and their interrelatedness); and naming the elements (developing a formulation of the identified dynamics). Eells et al [16] demonstrated that compared with non-experts, experts generated more forward (or inferential) reasoning in their case formulations, as opposed to backward (or deductive) reasoning. The authors added that to be effective, forward reasoning should be based on a well-developed and rich knowledge foundation, which supports the view that formal didactic teaching likely plays an important role in improving formulation skills [10,17].…”
Section: Approaches To Skills-based Formulation Teachingmentioning
confidence: 99%